CHARACTERISTICS OF STRUCTURAL COMPONENTS OF INTRAHEPATIC BILIARY TRACTS IN HUMANS - Dubinin, D.S.; Shepitko, V.I.; Dubinin, S.I.; Stetsuk, Ye.V.; Boruta, N.V.; Levchenko, O.A.; Ulanovska-Tsyba, N.A. (World of Medicine and Biology, 2023)
Among the most common diseases of the hepatobiliary system are chronic cholecystitis, cholangitis, gallstone disease, and post-cholecystectomy syndrome, which are increasingly prevalent. Gallstone disease affects more than 10 % of the adult population in various countries around the world. There is a doubling of the number of patients every ten years in all economically developed countries. This pathology is found in women 3–4 times more often than in men. The incidence of the disease increases with age. The intrahepatic bile ducts of humans consist of two layers: an outer adventitial layer and an inner mucosal layer. In the initial part of the liver's biliary system, the biliary pathways in the mucous membrane are composed of cuboidal epithelium resting on the basal membrane. In the middle section of the human biliary system, not only cuboidal but also columnar epithelial cells appear. In the terminal section of the biliary system, the number of columnar epithelial cells in the inner lining increases. Epithelial cells change their shape from cuboidal to columnar. The outer layer is composed of loose connective tissue, with fibroblastic cell rows and an intercellular substance containing collagen fibers and amorphous material.
Keywords: liver; bile ducts; cholecystitis; gallstone disease